EFEKTIVITAS SUPLEMENTASI BRANCHED-CHAIN AMINO ACID (BCAA) TERHADAP TIMBULNYA DELAYED ONSET MUSCLE SORENESS (DOMS) - Sanjaya, Evan Japutra; Ayusari, Amelya Aughustina; Ghozali, Dhoni Akbar; Wiboworini, Budiyanti (Journal of Nutrition College, 2021)
Background: Sensation in the form of pain, edema, and stiffness that increases 24-48 hours after high-intensity training, especially eccentric exercises is called Delayed Onset Muscle Soreness (DOMS). One method to accelerate the recovery process and reduce the pain caused by DOMS is with Branched-Chain Amino Acid (BCAA) supplementation. However, until now, there has been limited research that proves the difference in the effectiveness of supplementation time between before and after exercise. Objectives: The aim of this research was to determine the difference in the effectiveness of BCAA supplementation time on DOMS.Methods: This research was an experimental research. A posttest only control group design approach was carried out to measure the effectiveness of supplementation on DOMS as measured by VAS at 24 hours after exercise. A pre and post control group design approach was carried out to measure the effectiveness of supplementation on the alteration in Range of Motion (ROM) as measured by the modified Lower Extremity Functional Scale (LEFS) questionnaire before exercise and 24 hours after exercise. The subjects were classified into 3 groups, namely the control group, 30 minutes before exercise supplementation, and 1 hour after exercise supplementation. Data were analyzed by one way ANOVA and Kruskall Wallis tests. Results Total sample in this study was 30 people. The result of oneway ANOVA test for differences in the effectiveness of BCAA supplementation on VAS was p<0.001. The result of post hoc test between the control and before and after exercise supplementation group was p<0.001, while between the before and after supplementation group was p=0.113. The result of Kruskall Wallis test to measure the effectiveness of supplementation on the alteration (Î”) in LEFS was p=0.336Conclusion: There was no significant difference in the level of pain between the before and after BCAA supplemented group. However, there were significant differences in the level of pain in both of the before and after supplementation group with the control group. There was no significant differences in the alteration of ROM between the three groups